Electrode for electrochemical energy storage device

By mixing ultrafine active materials with adhesive to form composite particles and depositing them on the conductive substrate by electrostatic deposition process, the problems of high cost and poor performance of electrode manufacturing in the prior art are solved, efficient and cost-effective electrode manufacturing is achieved, and the overall performance of the electrochemical energy storage device is improved.

CN119631185APending Publication Date: 2025-03-14AM BATTERIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044732.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-06-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has problems of high cost and poor performance when manufacturing electrodes for electrochemical energy storage devices, especially when using ultrafine active materials, the transmission efficiency and coating consistency of the electrostatic deposition technology are insufficient.

Method used

By mixing ultrafine active material particles with one or more binder I materials to form agglomerates and combining with another or more binder II materials to form composite particles, the composite particles are deposited onto the conductive substrate by using an electrostatic deposition process to form an electrode coating with high transmission efficiency and consistency.

Benefits of technology

It realizes efficient and cost-effective electrode manufacturing, improves the transmission efficiency and coating consistency of the electrodes, and improves the overall performance of the electrochemical energy storage device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631185A_ABST
    Figure CN119631185A_ABST
Patent Text Reader

Abstract

An exemplary method of manufacturing an electrode for an electrochemical energy storage device is provided. The method includes forming agglomerates from ultrafine active particles comprising one or more binder I materials. The method includes forming composite particles by combining agglomerates with one or more binder II materials. The method includes depositing composite particles onto a conductive substrate by an electrostatic deposition process to form a coating. The method includes densifying the coating and the conductive substrate to form an electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 348,693, filed on June 3, 2022. The entire contents of the foregoing provisional application are incorporated herein by reference in their entirety. background 1. Technical Field

[0004] The present disclosure relates to systems and methods for making electrodes having particular utility in electrochemical energy storage devices, such as lithium-ion batteries, and to advantageous electrodes having beneficial property / performance attributes. 2. Background technology

[0005] Li-ion batteries are typically composed of a cathode, an anode, a separator, and an electrolyte. The cathode and anode may include a composite material layer coated on a current collector foil. The composite material layer is typically composed of an electrochemically active material as well as a conductive additive and a binder additive.

[0006] In a typical Li-ion battery, common active materials for the cathode are lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide (LCO) and lithium iron phosphate (LFP), while common anode active materials are based on carbonaceous materials such as graphite, silicon or silicon-based composites. The current collector materials for the cathode and anode are usually aluminum and copper, respectively.

[0007] The conventional electrode manufacturing method used to make cathodes and anodes is called slurry casting. In slurry casting, the binder additive material is paired with a liquid so that they can be combined into a uniform binder / solvent slurry. Afterwards, the active material and conductive additive are mixed into the slurry. This slurry is then deposited on a current collector foil and subsequently dried to remove the solvent.

[0008] Another method for manufacturing Li-ion batteries involves electrostatic spray deposition (ESD). There have been articles disclosing the use of ESD technology in solvent-free composite electrode coatings for Li-ion batteries. Solvent-free electrode coating technology is attractive because it can significantly reduce energy consumption in the manufacturing process and significantly reduce the manufacturing cost of the battery. In principle, since the composite electrode powder is deposited directly on the metal current collector by an electrostatic spray deposition process, the EDS technology allows for simpler and more flexible electrode coatings.

[0009] ESD is widely used for dry powder coating of metal parts. For ESD coating applications, coating quality and transfer efficiency are often directly related to the properties of the coating powder particles. A typical electrostatic deposition coating process generally involves feeding the coating powder from a hopper into an electrostatic deposition device, fluidizing the powder, electrostatically charging the fluidized powder particles, and allowing the charged particles to flow and travel in the electric field so that the charged particles reach and deposit onto a grounded conductive substrate.

[0010] A typical process for solvent-free electrostatic deposition coating for battery electrode manufacturing includes the following processing steps: (a) mixing electrochemically active material powder, binder material powder and conductive material powder to form a mixture with a specified stoichiometry; (b) feeding the mixture into an electrostatic deposition device and fluidizing it; (c) electrostatically charging the particles in the fluidized mixture; (d) causing the charged particles to flow and travel in an electric field so that the charged particles reach and deposit on a grounded current collector to form a deposited layer; (e) heating and compressing the coated current collector to form an electrode. The electrode can then be incorporated into a desired application environment, for example, the electrode can be used in battery cell manufacturing. Depending on the active material in the deposited layer, the electrode can be the cathode or anode of the battery.

[0011] Despite the efforts made to date, there remains a need for improved, cost-effective systems / methods for electrode manufacturing, and cost-effective electrodes that exhibit efficient performance properties / characteristics. These and other objects are achieved according to the systems / methods and electrodes disclosed herein. Summary of the invention

[0012] According to an embodiment of the present disclosure, an exemplary method for manufacturing an electrode for an electrochemical energy storage device is provided. The method includes forming agglomerates from ultrafine active particles containing one or more binder I materials. The method includes forming composite particles by combining the agglomerates with one or more binder II materials. The method includes depositing the composite particles onto a conductive substrate by an electrostatic deposition process to form a coating. The method includes densifying the coating and the conductive substrate to form an electrode.

[0013] In some embodiments, the average particle size (D50) of the ultrafine active particles is less than 5 μm. The ultrafine active particles are cathode materials or anode materials. In some embodiments, the cathode material can be selected from (i) lithium transition metal oxides, lithium transition metal sulfides, lithium polyanion cathode materials, or combinations thereof, wherein the lithium polyanion cathode materials include lithium transition metal phosphates, lithium transition metal silicates; or (ii) sodium transition metal oxides, sodium polyanion cathode materials, Prussian blue analog cathode materials, or combinations thereof.

[0014] In some embodiments, the anode material can be selected from (i) carbonaceous anode materials, graphite, Si, silicon-based composite materials, SiOx, lithium alloy materials, lithium transition metal oxide anode materials, or combinations thereof; or selected from (ii) sodium ion intercalation anode materials, including Prussian blue analog anodes and sodium metal transition metal oxide anodes.

[0015] In some embodiments, one or more adhesive I materials can be selected from one or more of polymer materials, conductive polymer materials, polymer electrolytes, solid electrolyte composite materials and carbonaceous materials. In some embodiments, polymer materials can be selected from polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, polymethyl methacrylate, polystyrene butadiene rubber adhesive, carboxymethyl cellulose adhesive, polyacrylic acid or a combination thereof. In some embodiments, one or more adhesive II materials can be selected from one or more of polymer materials, polymer electrolytes, solid electrolyte composite materials and carbonaceous materials. In some embodiments, one or more adhesive I and one or more adhesive II materials can be the same material. In some embodiments, one or more adhesive I and one or more adhesive II materials can be different materials.

[0016] In some embodiments, agglomerate can be formed by one or more adhesive I materials and one or more additives. In such embodiments, one or more additives can be a conductive material selected from carbon black, carbon nanofiber, carbon nanotube, graphene, graphite, metal powder or its combination. In some embodiments, composite particles can be formed by one or more adhesive II materials and one or more additional additives. In such embodiments, one or more additional additives can be a conductive material selected from carbon black, carbon nanofiber, carbon nanotube, graphene, graphite, metal powder or its combination. In some embodiments, the additional additives in agglomerate formulation and composite particle formulation can be the same. In some embodiments, the additional additives in agglomerate formulation and composite particle formulation can be different.

[0017] The method may include incorporating the electrode into a component selected from the group consisting of a rechargeable lithium battery, a lithium ion battery, a rechargeable lithium sulfur battery, a solid state battery, a rechargeable sodium battery, and a sodium ion battery.

[0018] According to embodiments of the present disclosure, exemplary electrodes formed by the exemplary methods discussed herein are provided.

[0019] According to an embodiment of the present disclosure, an exemplary method of making composite particles containing ultrafine active materials is provided. The method includes mixing ultrafine active material particles with one or more binder I materials to produce agglomerates. The method includes mixing the agglomerates with one or more binder II materials.

[0020] In some embodiments, the method may include mixing ultrafine active material particles with one or more binder I materials and one or more additives to produce agglomerates. In some embodiments, the method may include mixing agglomerates with one or more binder II materials and one or more additional additives. In some embodiments, one or more binder I materials are added as dry powders. In some embodiments, one or more binder I materials are added as solutions. In some embodiments, one or more binder I materials are added as suspensions. In some embodiments, mixing is performed with heating. In some embodiments, mixing is performed without heating.

[0021] Any combination and / or arrangement of the embodiments can be envisioned. Other objects and features will become apparent from the detailed description below in conjunction with the accompanying drawings. However, it should be understood that the drawings are designed only as examples, rather than as a definition of the limitations of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] To assist those skilled in the art in making and using the electrodes and related systems / methods, reference is made to the accompanying drawings, in which:

[0023] Figure 1A Schematic diagram of the dispersion pattern of particles in the composite electrode powder mixture obtained by dry blending.

[0024] Figure 1B Schematic diagram of ultrafine active material particles being processed into agglomerates of specified size.

[0025] Figure 1C Schematic diagram of composite particles formed by the combination and interaction of active material agglomerates with binder particles and conductive material particles.

[0026] Figure 2 Schematic diagram of the stoichiometry of the powder in the feedstock and the deposited layer.

[0027] Figure 3 Schematic diagram of the stoichiometry of the powders in the feedstock and the deposited layers, where the composite particles are fed into an electrostatic deposition apparatus for fluidization, electrostatic charging, and deposition onto a conductive substrate.

[0028] Figure 4A is the particle size distribution (PSD) diagram of nickel manganese cobalt oxide (NCM), Figure 4B is the PSD diagram of lithium cobalt oxide (LCO), Figure 4C is the PSD diagram of graphitized carbon (GC), Figure 4D It is the PSD diagram of lithium iron phosphate (LFP).

[0029] Figure 5It is a bulk density characteristic table of raw materials.

[0030] Fig. 6A is a scanning electron microscope (SEM) image of pristine LFP powder.

[0031] Figure 6B is a SEM image of LFP particle formation after 2 minutes.

[0032] Figure 6C is a SEM image of LFP particle formation after 4 minutes.

[0033] Fig.6D is a SEM image of LFP particle formation after 8 minutes.

[0034] Figure 7 This is a table of bulk density and packing ratio of granular LFP.

[0035] Fig. 8A is a SEM image of non-granular LFP.

[0036] Figure 8B is a SEM image of small particle LFP / PPA.

[0037] Figure 8C is a SEM image of the optimized LFP / PAA particles.

[0038] Fig.8D is the SEM image of LFP / PEO particles mixed with PVDF and C65.

[0039] Fig. 9 This is a solvent-free LFP electrode made from ultra-fine granular LFP.

[0040] Fig.10 It is the rate performance diagram of LFP electrode.

[0041] Fig.11A is a SEM image of a cross section of a solvent-free LFP electrode using ultrafine LFP.

[0042] Fig. 11B is a SEM image of the top surface of the solvent-free LFP electrode using ultrafine LFP. DETAILED DESCRIPTION

[0043] According to the present disclosure, an advantageous system / method for solvent-free electrostatic deposition (ESD) coating of battery electrodes is provided, which is based on ultrafine particle materials having high transfer efficiency and consistency, and technology for making electrode material particles suitable for the disclosed solvent-free ESD coating process from precursors having ultrafine active material powders.

[0044] Batteries typically include a cathode, an anode, a separator, and an electrolyte. In a typical battery, the cathode and anode are composed of a composite electrode powder mixture and a current collector. The composite electrode powder mixture typically contains active material particles (AM), binder material particles (Binder), and conductive material particles (CB). The active material provides electrochemical activity, such as providing energy for the battery. The binder material adheres the active material particles and the conductive material in the electrode so that the electrode has good mechanical stability, good ionic conductivity, and good electrical conductivity. The conductive material provides conductivity in the electrode. Both the binder material and the conductive material are typically electrochemically inert in the battery. Therefore, the binder and conductive material added to the electrode increase the total weight and volume of the battery, while reducing the weight energy density and volume energy density of the battery. Both the binder material and the conductive material need to exhibit the necessary level of chemical stability and electrochemical stability in the battery to ensure that the battery exhibits suitable performance and life.

[0045] In a typical Li-ion battery, the active electrode material is a cathode material, such as lithium nickel cobalt manganese oxide (NCM) or lithium iron phosphate (LFP), and an anode material based on a carbonaceous anode material, graphite, silicone resin or Si-based composite material. The current collector of the cathode is usually Al foil, and the current collector of the anode is usually Cu foil. The binder material is a polymer material, such as PVDF, PTFE, PEO, PMMA, SBR, CMC, etc., which are electrical insulators. The conductive material is usually conductive carbon black, carbon nanotubes or graphene. In addition, functional additives may be included in a typical composite electrode. These additives may be silicon dioxide, aluminum oxide, zirconium oxide or any combination thereof. The true density, conductivity and dielectric constant of the active material, binder material and conductive material are significantly different.

[0046] The mass ratio of active materials in the composite electrode is usually higher than 70%, and the mass ratio of binder and conductive material is usually lower than 30% so that the battery has sufficient gravimetric energy density and volumetric energy density as well as good power capacity.

[0047] Although Li-ion batteries use NCM cathode or graphite anode materials with typical particle sizes of 5-30 μm, in many cases, ultrafine particle active materials are used to enable the battery to meet performance requirements. The use of ultrafine particles as the starting material for the agglomerates of the present disclosure advantageously allows the electrolyte to easily access the ultrafine particles, so that the unique and beneficial properties of the ultrafine particles are retained in the agglomerate form. For example, ultrafine particles have short diffusion distances and small morphological changes, making them beneficial for fast charging or high power capacity. Therefore, retaining the beneficial properties of ultrafine active particles while overcoming the fundamental challenges of solvent-free manufacturing electrodes is the basis of the present disclosure.

[0048] Ultrafine particle size is defined hereinafter as an average particle size of less than 5 μm. For example, carbon-coated LFP nanoparticle materials in the size range of 100-1000 nm are used as cathodes in lithium-ion batteries because of the inherent low electronic and ionic conductivity of uncoated larger particle size LFP materials. Commercial PVDF binders are typically agglomerated with an average size of 1-30 μm. Some PVDF binder agglomerates include sub-particles with primary particle sizes of 100-1000 nm.

[0049] For conventional solvent-based slurry electrode coating technology, the PVDF binder is dissolved in the solvent NMP. Therefore, the sub-particle size of the PVDF agglomerates does not significantly affect the performance of the binder. However, for solvent-free electrode coating using electrostatic spray deposition technology, the binder in the composite electrode powder mixture consisting of active materials, binders and conductive materials usually needs to be depolymerized to form small sub-particles with a particle size of 100-1000nm to achieve effective bonding function. The conductive carbon particles used in solvent-based slurry coating or solvent-free ESD coating are also very small, typically in the range of 50-1000nm, so as to be able to establish an effective conductive network in the electrode.

[0050] During EDS, the charge of a particle is related to its relative dielectric constant and size via Equation I:

[0051]

[0052] Where r is the particle radius, E is the electric field strength, e is the electron charge, k is the electron mobility, n is the electron concentration, t is the time, ε0 is the absolute dielectric constant, ε r is the relative dielectric constant of the powder.

[0053] Equation 1 shows that the particle charge is proportional to the square of the particle size. Therefore, it is expected that ultrafine particle size significantly reduces its chargeability. Lower chargeability reduces the ability of the particles to deposit on the conductive substrate, resulting in low transfer efficiency and poor coating consistency. In addition, the mass of ultrafine particles is very low, which causes the charged particles to flow more randomly in the electric field due to aerodynamic effects. This results in fewer charged particles reaching the conductive substrate and depositing on it, resulting in low transfer efficiency.

[0054] The transfer efficiency is the ratio of the mass of electrostatically charged particles deposited on the conductive substrate to the total mass of the fluidized particles dispensed. Higher transfer efficiency means more particles are deposited on the conductive substrate, resulting in higher first-time utilization of the coated material. Therefore, high transfer efficiency of ESD technology applied to solvent-free electrode coating is crucial for efficient battery production.

[0055] The consistency of the deposited layer includes the stoichiometric consistency between the deposited layer and the raw material powder mixture, as well as the stoichiometric consistency and geometric consistency within the deposited layer. Any inconsistency in the deposited layer leads to inconsistency in the final battery electrode and ultimately reduces battery performance. Therefore, it is also crucial to ensure high consistency of the coating. In some embodiments, the high consistency of the coating can be a thickness or load variation of less than ±2% in the electrode during lithium-ion battery production.

[0056] The ability of a powder to fluidize and flow easily in an electric field, known as flowability, is affected by particle size. In general, smaller particle sizes have lower flowability, often driven by a higher degree of van der Waals interactions, resulting in greater powder cohesion. Low particle flowability reduces the number of charged particles that flow in the electric field, reach the conductive substrate, and deposit on it, resulting in low transfer efficiency.

[0057] According to the present disclosure, a well-mixed electrode powder mixture having defined stoichiometric amounts of active material, binder, and conductive material has a Figure 1A The particle dispersion pattern shown, in which the active material has an ultrafine particle size comparable to the ultrafine particle size of the binder particles and the conductive carbon particles. When the electrode powder mixture is deposited on the current collector using the ESD technique, the fluidized particles are charged separately, then flow and travel in the electric field, and finally those charged particles that reach the surface of the current collector are deposited on the current collector. Low transfer efficiency can be expected due to the low particle chargeability and low powder fluidity caused by the small (ultrafine) particle size. In addition, due to the significant differences in conductivity, density, chargeability and fluidity among the active material, binder and conductive material particles, the ratio of these particles deposited on the substrate, or the unit stoichiometry in the deposited layer, deviates from the original mixture, resulting in inconsistency in the deposited layer ( Figure 2 ). The unit volume stoichiometry is defined as the mass ratio of active material, binder and conductive material per unit area per unit thickness from the current collector to the outer surface of the deposited layer. The unit area is defined as 1 cm 2 , the unit thickness is defined as 50μm.

[0058] To address the problems associated with electrostatic deposition of ultrafine particulate active materials, a novel and advantageous process is disclosed herein.

[0059] In particular, the disclosed method comprises the following steps. In a first step, the method comprises processing ultrafine active material particles to form agglomerates ( Figure 1B The method includes combining and interacting active material agglomerates with binder particles and conductive material particles to form composite particles ( Figure 1C The method comprises feeding the composite particles into an electrostatic deposition apparatus for fluidization, electrostatic charging and deposition onto a conductive substrate ( Figure 3 ). The method includes heating and compressing a coated electrode including a deposited layer and a conductive substrate to form an electrode, such as a cathode or anode for battery manufacturing. The steps mentioned can be performed in the order listed above or in a variation of the order listed above.

[0060] The active material can be any type of cathode or anode material used in the industry for batteries. Batteries include primary batteries and rechargeable batteries. Rechargeable batteries include Li-ion batteries, rechargeable lithium batteries, all-solid-state batteries, polymer electrolyte batteries, rechargeable lithium-sulfur batteries, rechargeable sodium batteries, and sodium-ion batteries. For ease of description, Li-ion batteries are used for explanation below. However, it should be understood that the principles and processes discussed herein can also be applied to other types of batteries.

[0061] Common cathode materials in Li-ion batteries are lithium transition metal oxides and polyanion cathode materials, including lithium nickel cobalt manganese oxide (NCM), lithium iron phosphate (LFP), etc. Common anode materials in Li-ion batteries are carbonaceous materials, lithium alloy element-based materials, lithium transition metal oxides, including graphite, hard carbon, soft carbon, Si, Si / C composites, SiOx, SiOx / C composites, lithium titanium oxide, etc.

[0062] The exemplary method discussed herein uses two adhesives: Adhesive I and Adhesive II ( Figure 3 ). The function of the binder I is to bind the ultrafine active material particles to form agglomerates. Suitable binder I materials need to have sufficient binding ability to the ultrafine particles to form mechanically stable agglomerates, have chemical stability when the active material and other components contact the binder, and have electrochemical stability in the operating window of the battery cell. The binder material used as binder I can be selected from, for example, polymeric materials, carbonaceous materials, inorganic materials, etc.

[0063] According to the present disclosure, commonly used polymer binder I materials for Li-ion batteries include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyethylene glycol (PEG), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polymethyl methacrylate (PMMA), styrene-butadiene rubber (SBR), polyethylene (PE), etc. The binder I material may also be / include a conductive polymer, such as polypyrrole, polyaniline, etc. The carbonaceous binder may be a carbon network. The inorganic binder material includes lithium polysilicate (Li2Si5O 11 )、Sodium polyphosphate ((NaPO3) n ), lithium dihydrogen phosphate (H2LiPO4), etc. In some embodiments, the binder material can be a polymer electrolyte, a solid electrolyte, etc.

[0064] Most binder I materials are electrochemically inert. The binder I contained in the agglomerate increases the weight and volume, which reduces the energy of the active material delivered per unit weight or unit volume, such as the gravimetric energy density and the volumetric energy density. For this type of binder I material, it is preferred that the amount of binder I contained in the agglomerate is smaller. Typically, the mass ratio of binder I in the agglomerate is less than 30%, preferably not more than 10%. In some embodiments, the mass ratio of binder I in the agglomerate is, for example, about 0.1-30% (inclusive), 0.2-30% (inclusive), 0.3-30% (inclusive), 0.4-30% (inclusive), 0.5-30% (inclusive), 0.6-30% (inclusive), 0.7-30% (inclusive), 0.8-30% (inclusive), 0.9-30% (inclusive). ), 1-30% (inclusive), 2-30% (inclusive), 3-30% (inclusive), 4-30% (inclusive), 5-30% (inclusive), 10-30% (inclusive), 15-30% (inclusive), 20-30% (inclusive), 25-30% (inclusive), 0.1-30% (inclusive), 0.1-25% (inclusive), 0.1-20% ( Including end values), 0.1-15% (inclusive), 0.1-10% (inclusive), 0.1-5% (inclusive), 0.1-4% (inclusive), 0.1-3% (inclusive), 0.1-2% (inclusive), 0.1-1% (inclusive), 0.1-0.9% (inclusive), 0.1-0.8% (inclusive), 0.1-0.7% (inclusive), 0.1-0. 6% (inclusive), 0.1-0.5% (inclusive), 0.1-0.4% (inclusive), 0.1-0.3% (inclusive), 0.1-0.2% (inclusive), 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 10%, 15%, 20%, 25%, 30%, etc.

[0065] It is noteworthy that a binder I material that exhibits electrochemical activity can be selected that contributes electrochemical capacity and energy to the agglomerate. For example, an amorphous carbon binder for a composite anode particle composed of ultrafine graphite particles contributes some capacity. In this case, the contribution of electrochemical activity makes it feasible to include more binder I in the agglomerate. Generally, in the case where the binder I material contributes electrochemical activity, the mass ratio of the binder in the agglomerate is no more than 50%, preferably no more than 30%. In some embodiments, the mass ratio of the binder to the agglomerate is about, for example, 0.1-50% (inclusive), 0.2-50% (inclusive), 0.3-50% (inclusive), 0.4-50% (inclusive), 0.5-50% (inclusive), 0.6-50% (inclusive), 0.7-50% (inclusive), 0.8-50% (inclusive), 0.9-50% (inclusive), 1-50% (inclusive), 2-50% (inclusive), 3-5 0% (inclusive), 4-50% (inclusive), 5-50% (inclusive), 10-50% (inclusive), 15-50% (inclusive), 20-50% (inclusive), 25-50% (inclusive), 30-50% (inclusive), 35-50% (inclusive), 40-50% (inclusive), 45-50% (inclusive), 0.1-45% (inclusive), 0.1-40% (inclusive), 0.1-35% (inclusive) ), 0.1-30% (inclusive), 0.1-25% (inclusive), 0.1-20% (inclusive), 0.1-15% (inclusive), 0.1-10% (inclusive), 0.1-5% (inclusive), 0.1-4% (inclusive), 0.1-3% (inclusive), 0.1-2% (inclusive), 0.1-1% (inclusive), 0.1-0.9% (inclusive), 0.1-0.8% (inclusive), 0.1-0.7% (inclusive) %, 0.1-0.6% (inclusive), 0.1-0.5% (inclusive), 0.1-0.4% (inclusive), 0.1-0.3% (inclusive), 0.1-0.2% (inclusive), 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0066] In some cases, ultrafine particles of conductive material are incorporated into active material agglomerates ( Figure 1B) to increase the conductivity within the agglomerate. According to the present disclosure, the conductive material that can be incorporated into the agglomerate includes conductive carbon black, carbon nanotubes, graphene, conductive polymer particles or metal powder. The mass ratio of the conductive material in the agglomerate is generally not more than 10%, not more than 5%, and preferably 0.5-2%. In some embodiments, the mass ratio of the conductive material in the agglomerate can be about, for example, 0.1-10% (inclusive), 0.2-10% (inclusive), 0.3-10% (inclusive), 0.4-10% (inclusive), 0.5-10% (inclusive), 0.6-10% (inclusive), 0.7-10% (inclusive), 0.8-10% (inclusive), 0.9-10% (inclusive), 1-10% (inclusive), 2-10% (inclusive), 3-10% (inclusive), 4-10% (inclusive), 5-10% (inclusive), 6-10% (inclusive), 7-10% (inclusive), 8-10% (inclusive), 9-10% (inclusive), 0.1-9% (inclusive), 0.1-8% (inclusive), 0. 1-7% (inclusive), 0.1-6% (inclusive), 0.1-5% (inclusive), 0.1-4% (inclusive), 0.1-3% (inclusive), 0.1-2% (inclusive), 0.1-1% (inclusive), 0.1-0.9% (inclusive), 0.1-0.8% (inclusive), 0.1-0.7% (inclusive), 0.1-0.6% ( Including the end value), 0.1-0.5% (inclusive), 0.1-0.4% (inclusive), 0.1-0.3% (inclusive), 0.1-0.2% (inclusive), 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0067] Agglomeration of the ultrafine active material particles can be achieved by mixing the active particles with a melt of the binder I. In an exemplary implementation, the ultrafine particles are mixed with the molten binder in a mixer at a temperature above the melting point or softening point of the binder I. It is desirable that the melting or softening temperature of the binder I is above room temperature. If the melting or softening temperature is too low, agglomeration is unlikely to occur. When the melting / softening temperature is too high, a large amount of energy is consumed, which is generally undesirable. The preferred melting / softening temperature range of Adhesive I is, for example, about 50°C to 300°C (inclusive), 50°C-250°C (inclusive), 50°C-200°C (inclusive), 50°C-150°C (inclusive), 50°C-100°C (inclusive), 100°C-300°C (inclusive), 150°C-300°C (inclusive), 200°C-300°C (inclusive), 250°C-300°C (inclusive), 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, etc.

[0068] In some embodiments, the agglomeration of the ultrafine active material particles can be carried out by mixing the ultrafine active material particles with the binder I in a solution or suspension. The binder solution or suspension can be introduced into the mixer before or during the mixing process. The binder I can be dissolved in a solvent or suspended in a liquid medium. The solvent or liquid medium is usually evaporated during the mixing process with or without heating. The solvent or liquid medium can also be removed by heating after the mixing process.

[0069] In some embodiments, the agglomeration of ultrafine active material particles with binder I can be performed using a spray drying method. In an exemplary spray drying embodiment, ultrafine active material particles are suspended in a binder I solution. The suspension is dried by a spray drying process to produce agglomerates. Ultrafine active material particles and binder I particles can be uniformly suspended in a liquid medium. The suspension is dried by a spray drying process. In this case, the spray drying temperature is generally close to or slightly above the melting / softening temperature of binder I.

[0070] In some embodiments, ultrafine active material powders can be mixed with one or more precursors to form agglomerates, and the mixture can then be cured to form final active material agglomerates for ESD coatings. An example is nano-sized Si powder and fine graphite powder, which are mixed with asphalt at a temperature above the softening temperature of the asphalt to form initial agglomerates, and then carbonized at 70°C-1200°C to form Si / C agglomerates for ESD coatings.

[0071] In some cases, the ultrafine active material particles can interact with each other through cohesive forces to form mechanically stable agglomerates. In these cases, binder I is not required.

[0072] Therefore, the mixing method of ultrafine active material powder and adhesive I material can be selected from dry powder mixing and wet mixing. A typical dry powder mixing process includes first loading ultrafine active material powder and adhesive I powder into a mixer. Then mix the active material powder and adhesive powder combination under heating or without heating. A typical wet mixing process usually requires first loading the ultrafine active material powder into the mixer, and then introducing the adhesive I solution, suspension or melt into the mixer during the mixing process. The mixer can be any mechanical mixer and fluidized bed mixer, including impact mixer, shear mixer, such as Eirich mixer, mechanical fusion mixer, Cyclomix, etc.

[0073] The active substance agglomerates formed at least in part from the ultrafine active substance particles are further mixed with a binder material II and a conductive material in a defined stoichiometric amount to form composite particles according to the invention, such as Figure 1CAs shown. In the composite particles, binder II particles (usually characterized by very small particle size) and conductive material particles (usually also characterized by very small particle size) adhere to the surface of the active material agglomerate through physical and chemical interactions. The binder II particle size and the conductive material particle size are usually no more than 1000nm. In some embodiments, the binder II particle size and the conductive particle size can be, for example, about 30-1000 nm (inclusive), 40-1000 nm (inclusive), 50-1000 nm (inclusive), 60-1000 nm (inclusive), 70-1000 nm (inclusive), 80-1000 nm (inclusive), 90-1000 nm (inclusive), 100-1000 nm (inclusive), 200-1000 nm (inclusive), 300-1000 nm (inclusive), 400-1000 nm (inclusive), 500-1000 nm (inclusive), 600-1000 nm (inclusive), 700-1000 nm (inclusive), 800-1000 nm (inclusive), 900-1000 nm (inclusive), 30-900 nm (inclusive) ), 30-800nm ​​(inclusive), 30-700nm (inclusive), 30-600nm (inclusive), 30-500nm (inclusive), 30-400nm (inclusive), 30-300nm (inclusive), 30-200nm (inclusive), 30-100nm (inclusive), 30-90nm (inclusive), 30-80nm (inclusive), 30-70nm (including end values), 30-60nm (including end values), 30-50nm (including end values), 30-40nm (including end values), 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, etc.

[0074] Binder II materials can be selected from polymer materials, carbonaceous materials, inorganic materials, etc. (similar material categories to Binder I). Binder I and Binder II materials can be the same or different, depending on the materials used, process conditions, properties, their combinations, etc.

[0075] The conductive material in the composite particles can be a carbonaceous material, such as carbon nanotubes, carbon nanofibers, carbon black, graphene, graphite, etc. It can also be a metal particle, such as ultrafine particles of Al, Cu, etc. It can be an ultrafine conductive polymer particle. In some cases, a conductive material is not required, for example, for graphite or carbonaceous anodes, in some cases, a conductive material is not required because they are conductive. Therefore, in these cases, the composite particles only include active material agglomerates and binder II particles.

[0076] The composite particles are usually loaded in a hopper. They are fed into an electrostatic deposition device. In the ESD device, the composite particles are first fluidized, then charged by corona charging or friction charging, then flow in an electric field, and finally deposited on a grounded conductive substrate ( Figure 3 ).

[0077] It is critical that the active material agglomerates do not break during mixing, fluidization, electrostatic charging, flow and deposition on the conductive substrate. Therefore, these steps must be performed carefully to ensure the integrity of the active material agglomerates. In addition, it is also important that the composite particles do not break during mixing, fluidization, flow and deposition. Therefore, these steps must be performed carefully to ensure the integrity of the composite particles. This makes the unit stoichiometry in the deposited layer similar to (e.g., very close to) the original stoichiometry in the raw material powder. The mechanical stability of the active material agglomerates is a key factor affecting / maintaining the mechanical stability of the composite particles. The bonding effect of the binder I and the density of the active material play a key role in the mechanical stability of the active material agglomerates. The more pores in the agglomerate, the lower the mechanical stability of the agglomerate. The porosity in the agglomerate is generally not more than 70%. Preferably, the porosity is in the range of about, for example, 20-70% (inclusive), 20-60% (inclusive), 20-50% (inclusive), 20-40% (inclusive), 20-30% (inclusive), 30-70% (inclusive), 40-70% (inclusive), 50-70% (inclusive), 60-70% (inclusive), 20%, 30%, 40%, 50%, 60%, 70%, etc.

[0078] It is also critical that the composite particles have good chargeability. Good chargeability is achieved by increasing the particle size and the adhesion of the binder II particles to the surface. The mass of the composite particles is sufficient to avoid significant deviations of the charged particles from the deposition path in the electric field. This achieves high transport efficiency. The active material agglomerate size is in the range of 5-100 μm. Preferably, the active material agglomerate size is in the range of 10-30 μm. In some embodiments, the active material agglomerate size may be in the range of about: for example, 5-100 μm (inclusive), 10-100 μm (inclusive), 20-100 μm (inclusive), 30-100 μm (inclusive), 40-100 μm (inclusive), 50-100 μm (inclusive), 60-100 μm (inclusive), 70-100 μm (inclusive), 80-100 μm (inclusive), 90-100 μm (inclusive), m (including the end value), 10-90μm (including the end value), 10-80μm (including the end value), 10-70μm (including the end value), 10-60μm (including the end value), 10-50μm (including the end value), 10-40μm (including the end value), 10-30μm (including the end value), 10-20μm (including the end value), 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, etc.

[0079] The mixing methods that can be used to make the composite particles are similar to those disclosed for making active material agglomerates, for example, using dry powder or wet mixing methods. Preferably, no solvent is used in the mixing process.

[0080] In some embodiments, ultrafine active material powder is mixed with the first binder material (binder I) to form agglomerates. The ultrafine active material is a carbon-coated nanoparticle LFP with a particle size of 200-500nm. The binder I material is selected from PEG, PEO, PE or PVDF. The mass ratio of binder I in the active material and binder powder mixture is 1-10%. LFP and binder powder are loaded into an impact mixer, such as an Eirich mixer. The powder is mixed in a mixer at a temperature higher than the melting point of the binder, such as 70-100°C for PEG and PEO, 140-150°C for PE, and 180-200°C for PVDF.

[0081] In some embodiments, carbon-coated nanoparticles LFP with a particle size of 200-500 nm are loaded into a mixer. During the mixing process, a 10% PVDF / NMP solution is sprayed into the powder in the mixer. The mass ratio of dry PVDF in the active material and binder powder mixture is 1-10%. After mixing, the solvent is evaporated at about 100-150°C.

[0082] In an exemplary method for preparing composite particle powder for downstream processing, the prepared active material agglomerate powder is charged into a mixer together with PVDF powder having a primary particle size of 100-300 nm and carbon black having a primary particle size of 40-100 nm. The mass ratio of active material agglomerates in the mixture is 80-99%, the mass ratio of PVDF binder is 20-1%, and the mass ratio of carbon black is 20-1%. For example, the mixer can be an impact mixer or a shear mixer.

[0083] The composite particle powder is loaded into a hopper. The composite particle powder is fluidized by dry air and flows into a corona charging zone, which is generated by a corona induction electrode at a voltage of 10-100 kV. The preferred charging voltage is 20-50 kV. The charged composite particles travel in the electric field, reach the grounded aluminum foil current collector and are deposited on the current collector.

[0084] The coated electrode consisting of the deposited layers and the current collector can be first heated at a temperature above the melting point of PVDF, preferably 180-200°C, and then calendered at a temperature of 60-200°C with a defined calendering force to obtain the desired / designed electrode density. The pressed electrode is ready for lithium-ion battery assembly.

[0085] Example

[0086] Example 1.

[0087] 98 parts of carbon-coated LFP with a particle size D50 of about 1-2 μm and 2 parts of PVDF with a primary particle size of 200-500 nm were mixed in a high shear mixer at 120-170° C. for 10 minutes. After the mixture was cooled, 3 parts of PVDF and 2 parts of acetylene black with a primary particle size of 0-80 nm were added and mixed in a high shear mixer at room temperature for 10-20 minutes. The morphology of the powder mixture was studied by SEM.

[0088] The mixed LFP powder was loaded into the hopper of the electrostatic spray deposition system. The dry powder was fluidized by a carrier gas under vibration. The fluidized powder was charged by a corona electrostatic spray gun and deposited on a 15μm thick grounded aluminum foil. The coated side of the aluminum foil was pre-coated with a PVDF interfacial layer of less than 1μm thickness, which was applied using an electrostatic spray deposition technique. The deposited sample was placed on a hot plate and heated at 250°C for about 1 hour to melt the binder. Finally, the annealed sample was pressed to the desired thickness using a roller press to achieve a porosity of 35%. The electrode sample was ready for SEM / EDS, adhesion, and electrochemical characterization.

[0089] Comparative Example

[0090] 93 parts of carbon coated LFP with a particle size D50 of about 1 μm, 5 parts of PVDF and 2 parts of acetylene carbon black were added in a high shear mixer and mixed for 10-20 minutes at room temperature. The morphology of the powder mixture was studied by SEM.

[0091] The mixed LFP powder was loaded into the hopper of the electrostatic spray deposition system. The dry powder was fluidized by a carrier gas under vibration. The fluidized powder was charged by a corona electrostatic spray gun and deposited on a 15μm thick grounded aluminum foil. The coated side of the aluminum foil was pre-coated with a PVDF interfacial layer of less than 1μm thickness, which was applied using an electrostatic spray deposition technique. The deposited sample was placed on a hot plate and heated at 250°C for about 1 hour to melt the binder. Finally, the annealed sample was pressed to the desired thickness using a roller press to achieve a porosity of 35%. The electrode sample was ready for SEM / EDS, adhesion, and electrochemical characterization.

[0092] Granulation research

[0093] In an exemplary manufacturing process, the solvent is completely removed and the electrode powders (active materials, binders and conductive additives) are dry-mixed into a uniform mixture. To coat the powders onto the current collector, electrostatic deposition (ESD) is used. In this method, the dry particles are electrostatically charged and deposited on a grounded current collector. The chargeability of the particles depends on their size, with the particle charge being proportional to the square of the particle size.

[0094] Active materials such as NCM, LCO and graphite have been used to make solvent-free electrodes for batteries. The common feature of these materials is that the particle size is in the range of 5-30 μm ( Figure 4A -C). However, some active materials, such as LFP, are usually in the submicron size range ( Figure 4D Since chargeability is related to particle size, it is traditionally expected that LFP-based powder mixtures will be more difficult to charge. In this regard, ultrafine particles are defined as particles less than 5 μm in size (as used herein and as understood in the industry).

[0095] Particle size also affects the flowability of the powder. Flowability is also critical for powder feeding and electrostatic deposition. Generally, smaller particle size results in lower flowability and higher cohesion. One way to characterize flowability is to find the bulk density of the powder system. Figure 5 From the results in Figure 2, it is easy to notice that smaller LFP particles lead to a reduced packing fraction (the bulk density related to its theoretical density). Therefore, when using an LFP-based system, it can be expected that processability will be more difficult than with other powder systems.

[0096] To alleviate this problem, a method for making composite particles was developed. To achieve this, ultrafine particles are combined with a binder material to form composite particles of larger size. For example, LFP is mixed with polyacrylic acid (PAA) as a binder. In this example, PAA is dissolved in water to produce a solution with 5wt% PAA. This solution is added to a mixer containing crude LFP. The liquid / solid ratio for this example is 0.2 (2 parts liquid, 10 parts LFP). Therefore, the final composition of the LFP / PAA composite particles is 99wt% LFP and 1wt% PAA. In order to understand the granulation process, scanning electron microscope (SEM) images of the original LFP and LFP / PAA particles were taken. It can be seen that ( Fig. 6A ) The original LFP was indeed very small and consistent with the results of the PSD test. During the pelletizing process, multiple samples were saved to better understand how the particle formation changed over time. It is clear that particles are forming ( Figure 6B ), but the extended mixing time allows the particles to grow further. The additional time allows the already formed particles to collect smaller or unformed particles ( Figure 6C and 6D ).

[0097] After formation, the particles are mixed with polyvinylidene fluoride (PVDF) as a binder and super C65 carbon black (C65) as a conductive additive. The primary particle sizes of PVDF and C65 are 150nm and 50nm, respectively, which are significantly smaller than NCM or LCO. In the traditional method of mixing PVDF and C65 with NCM or LCO, the goal is to attach the additive material to the larger active material particles. Since it is difficult to achieve this attachment with ultrafine particles (such as original LFP), it becomes more important to achieve granulated LFP particles. First, the granulated LFP particles are mixed with 2wt% of PVDF and C65 each. It is important to mix at a high enough speed so that the secondary additive particles are fully broken down to their primary particle size. For initial electrode production, a high mixing tip speed (called LFP-PAA-1) is used. In order to understand the impact of granulation, the bulk density of LFP-PAA-1 and a benchmark mixture of 96wt.% LFP (non-granulated), 2wt.% PVDF and 2wt.% C65 (called BASE) were determined. Bulk density measurements of BASE LFP-PAA-1 ( Figure 7 ) are 0.340 g / cm 3 and 0.373 g / cm 3 The corresponding filling ratios to the bulk density measurements are 0% and 1%, respectively. As a reference, the filling ratio for a material system with an active material primary particle size in the range of 5-30 μm would be in the range of 20-30%.

[0098] The next step was to make electrodes using the BASE and LFP-PAA-1 powder systems. It was clear that the BASE system, without granulation, was difficult to spray with the ESD system. The electrode layer was significantly thicker than the NCM or LCO powder systems (thickness was about 2 mm). The LFP-PAA-1 powder system was also difficult to spray, given the similarity in bulk density. Based on the SEM images, it was also found that the particle sizes of the two materials were very similar ( Fig. 8A and 8B ). Compared with the original LFP particles ( Figures 6A-6D ), it was clear that the LFP had been broken up during the high-speed mixing process; therefore, the original LFP particles were mixed again with PVDF and C65, but at a lower tip speed to help retain the particle formation (referred to as LFP-PAA-2). Bulk density measurements showed a significant increase in bulk density to 1.03 g / cm 3 ( Figure 7 ), the corresponding filling rate is higher, which is 30%.

[0099] As expected, electrode fabrication with LFP-PAA-2 was significantly better than the previous LFP mix. The electrodes were easily made and were used for electrochemical testing. However, it was found that the larger LFP particles caused calendering issues and surface defects on the electrodes. To alleviate this issue, another batch of LFP particles was formed using the same method described previously. Afterwards, the size of the LFP particles was reduced to more closely resemble other types of active materials that did not require granulation. Size reduction was achieved by ensuring that the LFP particles were completely dry before adding them to the mixer. The mixing tip speed was selected so that the particles were not completely reduced to the original particle size, but rather high enough to effectively reduce the particle size.

[0100] Subsequently, the LFP particles were mixed with PVDF and C65 (referred to as LFP-PAA-3). The bulk density and packing ratio were found to be 0.559 g / cm 3 ( Figure 7 ), and the filling rate is 16%. Both values ​​are between the two extremes of the smallest particles (LFP-PAA-1) and the oversized particles (LFP-PAA-2). SEM image ( Figure 8C ) also shows particle sizes between the two extremes ( Figure 8B The smallest particle and Fig.8D Fabrication of electrodes using LFP-PAA-3 can be easily accomplished ( Fig. 9 ).

[0101] To demonstrate that the pelletizing binders are interchangeable, polyethylene oxide (PEO) was used instead of PAA and the process was repeated (referred to as LFP-PEO-1). Fig.8D It can be seen that the final granulation particle size is Figure 8CThe particle size of LFP-PAA-3 is similar. The bulk density and filling rate of the LFP-PEO system are also similar, which are 0.655 g / cm 3 and 19%. The electrode fabrication was also easily accomplished and used for electrochemical testing.

[0102] The testing of the electrodes started with adhesion testing. A slurry cast LFP electrode was prepared as a comparison point. The pull-off failure force of the slurry cast LFP electrode was equal to about 39.3N, while the failure force of the LFP-PAA-3 electrode was equal to about 37.1N. The LFP-PEO-1 electrode was significantly lower at 18.9N. Although the PEO electrode had lower adhesion properties, it was still strong enough to be handled and used for electrochemical testing.

[0103] Rate performance was achieved on all electrodes detailed previously. All electrodes showed relatively similar performance compared to the slurry cast control electrode ( Fig.10 ). Fig.11A and 11B Cross-sectional and top surface SEM images of solvent-free LFP electrodes using ultrafine LFP are provided.

[0104] In summary, this study achieved several goals. First, composite particles with ultrafine active materials and binders were successfully prepared. Next, the granular particles showed better processability (chargeability and flowability) compared to non-granular ultrafine particles. Finally, it was shown that the granular powder system exhibited similar mechanical and electrochemical properties compared to electrodes made using a conventional slurry casting process.

[0105] Although exemplary embodiments have been described herein, it is expressly noted that these embodiments should not be construed as limiting, but rather additions and modifications to the contents expressly described herein are also included within the scope of the present invention. In addition, it should be understood that the features of the various embodiments described herein are not mutually exclusive and may exist in various combinations and permutations, even if such combinations or permutations are not expressly indicated herein, without departing from the spirit and scope of the present invention.

Claims

1. A method for manufacturing an electrode for an electrochemical energy storage device, the method comprising: a. agglomerates formed by ultrafine active particles comprising one or more binder materials I; b. forming composite particles by combining the agglomerates with one or more binder II materials; c. depositing the composite particles onto a conductive substrate by an electrostatic deposition process to form a coating; and d. Densification of the coating and conductive substrate to form an electrode.

2. The method according to claim 1, wherein the average particle size (D50) of the ultrafine active particles is less than 5 μm.

3. The method according to claim 1, wherein the ultrafine active particles are cathode materials or anode materials.

4. The method according to claim 3, wherein the cathode material is selected from (i) lithium transition metal oxides, lithium transition metal sulfides, lithium polyanion cathode materials, or combinations thereof, wherein the lithium polyanion cathode materials include lithium transition metal phosphates and lithium transition metal silicates; or selected from (ii) sodium transition metal oxides, sodium polyanion cathode materials, Prussian blue analog cathode materials, or combinations thereof.

5. The method according to claim 3, wherein the anode material is selected from (i) carbonaceous anode materials, graphite, Si, silicon-based composite materials, SiOx, lithium alloy materials, lithium transition metal oxide anode materials, or combinations thereof; or selected from (ii) sodium ion intercalation anode materials, including Prussian blue analog anodes and sodium metal transition metal oxide anodes.

6. The method according to claim 1, wherein the one or more binder I materials are selected from one or more of polymer materials, conductive polymer materials, polymer electrolytes, solid electrolyte composite materials and carbonaceous materials.

7. The method according to claim 6, wherein the polymer material is selected from polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, polymethyl methacrylate, polystyrene butadiene rubber binder, carboxymethyl cellulose binder, polyacrylic acid or a combination thereof.

8. The method of claim 1, wherein the one or more Binder II materials are selected from one or more of polymer materials, polymer electrolytes, solid electrolyte composites, and carbonaceous materials.

9. The method of claim 1, wherein the one or more Adhesive I and one or more Adhesive II materials are the same material.

10. The method of claim 1, wherein the one or more Adhesive I and one or more Adhesive II materials are different materials.

11. The method of claim 1 , wherein the agglomerates are formed from one or more Binder I materials and one or more additives.

12. The method of claim 11, wherein the one or more additives are conductive materials selected from carbon black, carbon nanofibers, carbon nanotubes, graphene, graphite, metal powders, or combinations thereof.

13. The method of claim 1, wherein the composite particles are formed from one or more Binder II materials and one or more additional additives.

14. The method of claim 13, wherein the one or more additional additives are conductive materials selected from carbon black, carbon nanofibers, carbon nanotubes, graphene, graphite, metal powders, or combinations thereof.

15. The method of claim 1, further comprising incorporating the electrode into a component selected from the group consisting of a rechargeable lithium battery, a lithium ion battery, a rechargeable lithium sulfur battery, a solid state battery, a rechargeable sodium battery, and a sodium ion battery.

16. An electrode formed by the method of claim 1.

17. A method of making composite particles comprising ultrafine active materials, the method comprising: (i) mixing ultrafine active material particles with one or more binder I materials to produce agglomerates; and (ii) mixing the agglomerates with one or more Binder II materials.

18. A method according to claim 17, comprising mixing the ultrafine active material particles with one or more binder I materials and one or more additives in step (i) to produce agglomerates.

19. A method according to claim 17 comprising mixing the agglomerates with one or more Binder II materials and one or more additional additives in step (ii).

20. The method of claim 17, wherein the one or more Adhesive I materials are added as a dry powder.

21. The method of claim 17, wherein the one or more Adhesive I materials are added as a solution.

22. The method of claim 17, wherein the one or more Adhesive I materials are added as a suspension.

23. The method of claim 17, wherein the mixing in step (i) is performed under heating.

24. The method of claim 17, wherein the mixing in step (i) is performed without heating.